Simulation of the Operation of a Borehole Groundwater Intake with an Annular Prefabricated Conduit - V. V. Veremenyuk; V. V. Ivashechkin; V. I. Krytskaya (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
Among the considered options for schemes of prefabricated water conduits of borehole water intakes, the main ones are linear and ring schemes. The article presents a comparative analysis of the linear and ring schemes for the placement of prefabricated water conduits when choosing an option for designing a group well water intake with a circular arrangement of wells. It is founded that a small water intake with individual radial connections to the prefabricated unit can have advantages in reducing energy consumption for water transportation as compared to a water intake with an annular prefabricated conduit, which in any case should be justified by a feasibility comparison of options, which is based on hydraulic calculation water supply systems. Equations have been obtained for calculating the pumping rates of water intake wells with linear prefabricated conduits. It is shown that in an annular prefabricated conduit, in contrast to a linear one, in which the direction of movement of water flows is unambiguously known, there is always a point of separation of two flows directed along the ring to the prefabricated unit clockwise and counterclockwise, which makes it difficult to calculate such water intakes. Moreover, the position of this point depends on the number of water intake wells involved in the work and the parameters of the pipes connecting the sections of the water conduit. The absence of algorithms for calculating the ring prefabricated conduit with non-fixed flow rates at the well connection points complicates the hydraulic calculation, and, hence, finding the optimal water intake option. The article presents an algorithm for the hydraulic calculation of a water intake with a single-ring prefabricated conduit, which is based on the equation for the equality of pressure losses when water moves from the point of separation of two flows to the prefabricated unit along various paths and the continuity equation. The resulting algorithm can be easily extended to any number of wells. A numerical example of the hydraulic calculation of a group water intake, consisting of eight wells connected to an annular prefabricated, is considered.